Effect of bilayer coating composed of polyvinyl alcohol, chitosan, and sodium alginate on salted duck eggs. Issue 1 (1st January 2018) - Jiang, Yongli; Zhuang, Chenjun; Zhong, Yu; Zhao, Yanyun; Deng, Yun; Gao, Haiyan; Chen, Hangjun; Mu, Honglei
ABSTRACT: The composite bilayer film based on polyvinyl alcohol, sodium alginate, and chitosan were developed in this study, and the effects of the related coating on internal-quality changes of salted duck eggs (SDEs) during storage were determined. The results showed that the overall properties of the bilayer film were better than those of monolayer films, including storage stability. Coatings could significantly ( p  < 0.05) reduce quality deterioration of SDEs such as water loss, oil exudation, and gritty. The bilayer coating was more effective in inhibiting the increase of egg yolk pH and total bacterial counts than monolayer coatings. After storage for 60 days, water content of bilayer coated SEDs was 19.7% higher than that of the control SDEs, oil exudation was 38% higher, and gritty texture was 27.9% higher. Moreover, bilayer coating could prolong the shelf life of SDEs to more than 60 days at 25°C and 50% relative humidity according to the results of total bacterial count experiment, while the shelf life of control SDEs was less than 45 days. This study indicated the potential application of bilayer composite coating for preservation of SDEs.